Synchrotron radiation shielding design and ICRP radiological protection quantities. (23rd April 2015) - Bassey, Bassey; Moreno, Beatriz; Chapman, Dean
Abstract: Protection and operational quantities as defined by the International Commission on Radiological Protection (ICRP) and the International Commission on Radiation Units and Measurements (ICRU) are the two sets of quantities recommended for use in radiological protection for external radiation. Since the '80s, the protection quantities have evolved from the concept of dose equivalent to effective dose equivalent to effective dose, and the associated conversion coefficients have undergone changes. In this work, the influence of three different versions of ICRP photon dose conversion coefficients in the synchrotron radiation shielding calculations of an experimental enclosure has been examined. The versions are effective dose equivalent (ICRP Publication 51), effective dose (ICRP Publication 74), and effective dose (ICRP Publication 116) conversion coefficients. The sources of the synchrotron radiation white beam into the enclosure were a bending magnet, an undulator and a wiggler. The ranges of photons energy from these sources were 10–200 keV for the bending magnet and undulator, and 10–500 keV for the wiggler. The design criterion aimed a radiation leakage less than 0.5  µ Sv h −1 from the enclosure. As expected, larger conversion coefficients in ICRP Publication 51 lead to higher calculated dose rates. However, the percentage differences among the calculated dose rates get smaller once shielding is added, and the choice of conversion coefficients set did not affect the final shielding decision.